Oil removal from spent bleaching earth of vegetable oil refinery plant using supercritical carbon dioxide - Siti Machmudah; Nabil Apta Maulana; Andhika Shafian Maindo Norman; Valencia Marchilia Nyoto; Irji Amrullah; Wahyudiono; Sugeng Winardi; I Gede Wenten; Motonobu Goto (Heliyon, 2022)
The oil in the spent bleaching earth (SBE) matrix was successfully removed by applying the supercritical carbon dioxide (SCCO2) extraction technique in a semi-continuous flow–type system. The SCCO2 extraction process was conducted at 40–80 °C and 20–30 MPa with extraction time of ∼180 min. The color of SBE matrix changes from the dark to dark-pale color after the SCCO2 extraction treatment exhibiting the substances including oil in the SBE matrix were successfully removed. The extracted oil yield was around 95% when the SCCO2 extraction process was performed at 40 °C and 30 MPa with 10% ethanol addition as a co–solvent. The GC analysis showed that the prominent fatty acid constituents in the extracted oil are palmitic and oleic acids, furthermore it can be fed as a feedstock to produce biodiesel fuel. Next, it can be proposed that SCCO2 extraction system is a viable way to extract oil from the SBE matrix.